Treatment-related toxicity in men who received Intensity-modulated versus 3D-conformal radiotherapy after radical prostatectomy: A national population-based study. Issue 2 (August 2018) - Sujenthiran, Arunan; Nossiter, Julie; Parry, Matthew; Charman, Susan C.; Cathcart, Paul J.; van der Meulen, Jan; Clarke, Noel W.; Payne, Heather; Aggarwal, Ajay
Abstract: Background and purpose: In the post-prostatectomy setting the value of Intensity-modulated (IMRT) relative to 3D-conformal radiotherapy (3D-CRT) in reducing toxicity remains unclear. We compared genitourinary (GU) and gastrointestinal (GI) toxicity after post-prostatectomy IMRT or 3D-CRT. Materials and methods: A population-based study of all patients treated with post-prostatectomy 3D-CRT ( n = 2422) and IMRT ( n = 603) was conducted between January 1 2010 and December 31 2013 in the English National Health Service. We identified severe GI and GU toxicity using a validated coding-framework and compared IMRT and 3D-CRT using a competing-risks proportional hazards regression analysis. Results: There was no difference in GI toxicity between patients who received IMRT and 3D-CRT (3D-CRT: 5.8 events/100 person-years; IMRT: 5.5 events/100 person-years; adjusted HR: 0.85, 95%CI: 0.63–1.13; p = 0.26). The GU toxicity rate was lower with IMRT but this effect was not statistically significant (3D-CRT: 5.4 events/100 person-years; IMRT: 3.8 events/100 person-years; adjusted HR: 0.76, 95%CI: 0.55–1.03; p = 0.08). Conclusions: The use of post-prostatectomy IMRT compared to 3D-CRT is not associated with a statistically significant reduction in rates of severe GU and GI toxicity, although there is some evidence that GU toxicity is lower with IMRT. We would caution against rapid transition to post-prostatectomy IMRT until further evidence is available supporting its superiority.